Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

Risk challenge in sustainable development: Volatility spillover networks and systemic importance of China’s new energy companies - Yawei Guo; Boxin Zhu; Youfen Lin; Ningli Wang (Environment, Development and Sustainability, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

Retraction Note: Coordination evaluation of urban tourism and urban development based on TOPSIS method—a case of Xiamen city - Chunxia Zheng; Yawei Wu; Yanqing Lin; Yawen Zheng (Environmental Science and Pollution Research, 2024)

Experimental investigation for the effect of bust pressure on hydrogen explosion venting - Yawei Lu; Rujia Fan; Zhirong Wang; Xingyan Cao; Yongjun Li; Chendi Lin; Zhuohua Yang (Fuel, 2024)

Inactivation of Salmonella and Shiga-toxin producing Escherichia coli on soft wheat kernels using vacuum steam pasteurization - Yawei Lin; Quincy Suehr; Kirk Dolan; Senay Simsek; Teresa M. Bergholz (International Journal of Food Microbiology, 2023)

Bioconcentration of polycyclic aromatic hydrocarbons in different tissues of zebrafish (Danio rerio) investigated with PBTK model - Yawei Zhai; Haotian Wang; Xiaohan Lin; Xinghui Xia (Environmental Science and Pollution Research, 2023)

Identification of lower brominated bisphenol A analogs as the photooxidation products of tetrabromobisphenol A bis(2,3-dibromopropyl) ether (TBBPA-BDBPE) - Yuqing Jiang; Ling Wang; Minggang Zheng; Yongfeng Lin; Aifeng Liu; Yawei Wang; Ying Li (Science of The Total Environment, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Fate of salmonella and shiga-toxin producing Escherichia coli on wheat grain during tempering - Yawei Lin; Senay Simsek; Teresa M. Bergholz (Food Microbiology, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

RETRACTED ARTICLE: Coordination evaluation of urban tourism and urban development based on TOPSIS method—a case of Xiamen city - Chunxia Zheng; Yawei Wu; Yanqing Lin; Yawen Zheng (Environmental Science and Pollution Research, 2023)

Flood Risk Quantification, Transmission, and Propagation Analysis for Flood Water Utilization of Parallel Reservoirs - Wei Ding; Chi Zhang; Jie Lin; Xi Zhao; Yawei Ning; Huicheng Zhou (Journal of Hydrology, 2023)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

CRISPR-Cas9-Mediated Gene Therapy in Neurological Disorders - Lihong Guan; Yawei Han; Ciqing Yang; Suxiang Lu; Jiang Du; Han Li; Juntang Lin (Molecular Neurobiology, 2022)

Winner takes all: reconstructing the decapitation of a warrior in Bronze Age China from osteological evidence - Yawei Zhou; Shuang Lin; Rangping Qin; Hui-Yuan Yeh; Qun Zhang (Archaeological and Anthropological Sciences, 2020)
Decapitation is an ancient practice in Asia with inadequate research. The present study reports on the osteological examination of a headless skeleton excavated from a high-status tomb in Chu State style dating back to the late Warring States Period (ca. 3th century BC) in Lu’an, Anhui, China. The individual is identified as a victim of decapitation with five peri-mortem sharp force cut marks on the posterior parts of the cervical vertebrae, and another one on the right second metacarpal. Microscopic observation of the kerfs, the historical records and archaeological evidence support the speculation that the individual could be a warrior of Chu State, who is decapitated after being wounded during the war against the Qin State. The hacking implement and the sequences of the cut marks are further discussed to reconstruct the process of execution. This multidisciplinary reconstruction is the first scientific osteological analysis of the decapitation on the human remains from the Chinese Bronze Age. Moreover, it will enrich our knowledge of the decapitation phenomenon in terms of war and execution in ancient China.

Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.